أساليب القرآن في خطاب غير المسلمين وتوظيفها المعاصر : دراسة موضوعية تحليلية - مولود لك، زوراب إبراهيم (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This research aims at identifying and analyzing the types of Qur'anic styles of discourse with non-Muslims and suggesting how to apply them in modern times by using state-of-the-art means of communication. It is well-known that the styles of discourse in the Qur'an vary with the categories of non-Muslims, polytheists, Jews, Christians, hypocrites, Mandaeans, Magians and atheists. An attempt has been made in the research to highlight this dimension of the Qur'anic discourse with non- Muslims. The researcher reached a number of valuable findings. One of them is the wisdom behind the diversity of Qur'anic styles in addressing non-Muslims. It has been recommended in the conclusion of the research that the Qur'anic styles in addressing non-Muslims must be seriously taken care of by preachers who are concerned with calling non-Muslims to Islam. It is because these styles of discourse are natural and in accordance with human psyche. Time and again it has been proven that application of these Qur'anic styles of discourse with non-Muslims is highly result-oriented. In order to enhance the efficacy of the Qur'anic styles of discourse it has been recommended that every assiduous preacher should incorporate them in the communication with non-Muslims through modern means of communication like the Internet, satellite, slides, videos, recordings and other new techniques according to the progress of technology.